Penerapan Chatbot Telegram pada Sistem Pakar untuk Mendeteksi Kerusakan Sepeda Motor dengan Metode Depth-first Search - Kadek Darmaastawan (G-Tech: Jurnal Teknologi Terapan, 2024)
An expert system is a system that imitates the ability of experts. Previous research has built web and mobile-based expert systems in various fields. The weakness of web and mobile-based expert systems is that their development requires more time and effort to create the interface. Another disadvantage is that expert system users have to learn less common interfaces. The solution to this problem is to use a chatbot. The developers do not need to develop interfaces. Users also don't need to learn a new interface because people are already used to the chat application. This research builds an expert system for detecting motorbike damage using the Depth-first Search method based on the Telegram chatbot. The trial results in this research show an accuracy level of up to 90%. Therefore, the research succeeded in building a Telegram chatbot-based expert system that has good quality and benefits developers and users.